UTILIZATION OF FLIPBOOK AUDIO-VISUAL IN EBOOK INNOVATION TO IMPROVE STUDENT UNDERSTANDING FOR ACCOUNTING SUBJECTS IN SMK ARIF RAHMAN HAKIM SURABAYA - Komarun Zaman; Lis Setyowati; Devangga Putra Adhitya Pratama (CV Pena Jaya Pers, 2024)
In this study, an audio-visual flipbook-based e-module product was developed for the ledger material of accounting subjects studied by students at SMK Arif Rahman Hakim Surabaya. The Borg & Gall model was used in this development research. Furthermore, quantitative and qualitative data types were used with a Likert scale, and the data collection tool was a validation sheet. The data were analyzed by descriptive data analysis technique. Furthermore, three validators-material expert, media design expert, and language expert-tested the developed module according to their expertise. To ensure that the learning E-module was feasible, a validation test was conducted. An innovative and creative audio-visual flipbook-based E-module should be developed based on the problem. Further in this article, researchers will discuss the product validity of their audio visual flipbook-based e-modules. The validation test results are as follows: material expert validation results of 84 percent, media design experts of 83 percent, language experts of 81.5 percent, and the average validation results from student responses of 76.9 percent. By considering the criteria for the level of validity of the product, it can be concluded that the e-module product based on audio-visual flipbooks in general ledger accounting lessons is feasible to be widely tested at a later stage